An annotated check list of flat bugs (Hemiptera: Aradidae) from Vietnam - Pham, Minhlan; Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2011)
The flat bugs reported so far from Vietnam are cataloged. Altogther, 46 species of 5 subfamilies (Aneurinae, Aradinae, Calisiinae, Carventinae, Mezirinae) and 25 genera have been recorded for the Vietnamese fauna to date. Synonyms and distribution of each species are given. The type information for species originally described from Vietnam is provided.